2023
DOI: 10.1161/circulationaha.123.064053
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Door-to-Needle Times Are Associated With Better Outcomes After Intravenous Thrombolytic Therapy and Endovascular Thrombectomy for Acute Ischemic Stroke

Abstract: BACKGROUND: Existing data and clinical trials could not determine whether faster intravenous thrombolytic therapy (IVT) translates into better long-term functional outcomes after acute ischemic stroke among those treated with endovascular thrombectomy (EVT). Patient-level national data can provide the required large population to study the associations between earlier IVT, versus later, with longitudinal functional outcomes and mortality in patients receiving IVT+EVT combined treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke (HERMES) Collaborators found that the rates of good outcomes declined more rapidly in patients undergoing thrombectomy who received IVT than in patients ineligible for IVT, suggesting a potential differential effect of time. In addition, recent observational registry data from the US showed that shorter times from door to administration of IVT were associated with improved outcomes in patients undergoing thrombectomy …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke (HERMES) Collaborators found that the rates of good outcomes declined more rapidly in patients undergoing thrombectomy who received IVT than in patients ineligible for IVT, suggesting a potential differential effect of time. In addition, recent observational registry data from the US showed that shorter times from door to administration of IVT were associated with improved outcomes in patients undergoing thrombectomy …”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent observational registry data from the US showed that shorter times from door to administration of IVT were associated with improved outcomes in patients undergoing thrombectomy. 7 After the publication of the HERMES results, 6,21 theoretical considerations for and against the use of IVT before thrombectomy were presented. 4,26 This equipoise was not only theoretical, but shared among treating physicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intravenous thrombolysis (IVT) has been shown to improve outcomes in appropriately selected patients when administered within 4.5 hours of stroke onset . The benefits of thrombolysis are time dependent, and earlier treatment is associated with better outcomes . However, historically, only 20% to 30% of patients received thrombolysis within a door-to-needle (DTN) time of 60 minutes .…”
Section: Introductionmentioning
confidence: 99%